PENERAPAN KONSEP DANA DARURAT UNTUK MENINGKATKAN KETAHANAN FINANSIAL KELUARGA - Nurhayati; Helda Jaya Puspita, Helda Jaya Puspita (Forum Komunikasi Dosen, 2024)
This community service aims to improve the financial resilience of families through education for housewives (IRT) in one of the districts in Padang City. As the primary managers of family finances, housewives play a crucial role in ensuring the economic stability of the household. This activity focuses on educating participants about the importance of an emergency fund, ideally amounting to 6 to 12 times their monthly routine expenses, and how to set aside income to build this fund. In addition, participants were also educated about potential opportunities for increasing household income, such as small home-based businesses and utilizing technology. The educational session was conducted interactively using practical approaches that are easy to implement. Participants showed high enthusiasm for the material, especially in understanding the importance of sound financial planning and strategies to optimize family income potential. Through this activity, it is hoped that housewives can start building their family’s financial resilience while also improving their quality of life by maximizing additional sources of income.